ANALYSIS OF SEDIMENT MOVEMENT IN A RIVER DIVERSION SYSTEM - Agus Safari (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
Sediment-related disaster especially debris flow occurs frequently in various places in Indonesia. It has been well known in general that debris flow contents big size of materials which huge power to destroy the river and surrounding area. Comprehensive measures and rising awareness to prevent the toll of human lives against sediment disaster is considered necessary. Diversion system to proximate river aimed to lessen sediment load by considering its capacities and sediment prevention facilities becomes an alternative counter measure of sediment flood disaster. Information of river diversion capability and associated phenomena due to sediment gravity flow is a fundamental desire for establishing reasonable sediment control plans. Physical model compared to simple mathematical model are conducted to know river diversion capacity to convey sediment. The experiment used a channel made of masonry with 80 cm wide in average and 400 cm length, and 10 % gradient. The proposed sediment control facilities comprises two types, there are open type dam with 33 cm wide, 16cm high (at +1.245m elevation of crest) and four slits in main stream river and close type dam 41 cm wide, 15 cm high (at +1.255m elevation of spillway) for river diversion. The distance of these facilities is 110 cm. The result of this study is expected to be able to explain the sediment gravity flow behavior in the field. It shows that the performance of river diversion and open type dam control volume depend on quantity and mechanism of sediment flow from upstream, and also elevation of crest of the open type dam. The largest amount of sediment gravity flow entering diversion channel is about 7 % of sediment inflow for +1245 m open dam crest elevation and +1255 m river diversion spillway elevation.Keywords: Natural disaster, sediment, river diversion system.